Design and Evaluation of Different Transdermal Therapeutic Systems of Promethazine Hydrochloride - Shirisha, Suddala; Sahoo, Sunit Kumar; Veena, Tallam; Rao, Yamsani Madhusudan (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Promethazine Hydrochloride is a water-soluble drug and it suffers from poor bioavailability (25%) when given through oral route due to extensive first-pass metabolism. To overcome hepatic first pass metabolism and to enhance bioavailability, transdermal drug delivery systems (patches and gels) can be exploited. Objectives: The present work describes the transdermal permeation of anti-emetic agent promethazine hydrochloride and its transdermal delivery using transdermal patches and gels. For this investigation, HPMC E5, HPMC E50, and HPMC E15 used as a hydrophilic polymer for patch preparation and carbopol and xanthum gum acting as gel forming agent for hydrogel preparation. Materials and Methods: Permeability of promethazine hydrochloride was first investigated ex vivo using a rat abdominal skin. Then, transdermal gels and patches were developed using various polymers. Matrix diffusion mediated transdermal patches of promethazine can be formulated using polymers HPMC E5, HPMC E50, and HPMC E15 by solvent casting method. Matrix diffusion mediated transdermal gels of promethazine can be formulated using polymer carbopol and xanthan gum. Physicochemical interaction between drug and polymers were examined by Fourier Transform Infrared Spectroscopy (FTIR) and ex vivo permeation and in vitro drug release studies are conducted with the prepared formulations. Results: Transdermal patches of promethazine have reliable mechanical properties measured in terms of tensile strength (formulation F10 and F11 exhibited tensile strength values 0.0788±0.0014 kg/mm2 and 0.0652±0.0018 kg/mm2) as well as elongation at break values (1.1252±0.073% mm-2 and 0.8749±0.059% mm-2 respectively) can be generated with HPMC polymers. In vitro release trials show the adequacy of formulations formulated for the release of promethazine hydrochloride. The satisfactory percentage drug release was obtained from optimized formulation F1 (87.09±2.9), F7 (75.69±1.65), and F12 (94.69±1.9). Based on ex vivo release data menthol when used as a permeation enhancer, the flux 1.4 fold enhanced in transdermal patches and 1.9 folds enhanced in gels. Transdermal gels of carbopol showed the highest flux among all the formulations (F16 showed flux 117.5 μg/ cm2 /h). Conclusion: The results may be extrapolated to human beings as the permeability and structure of rat skin is identical to that of human beings. With decreased doses of these drugs and consequently reduced side effects, the development of the transdermal patches and gels for promethazine may thus be a promising one.
Keywords: Enhancement ratio; Flux; Promethazine Hydrochloride; Permeation; Transdermal; patches; Transdermal gels